Social Media Strategies Driving User Engagement in Academic Libraries: Social Media Strategies Driving User Engagement in Academic Libraries - Trisilya, Erlina Ayu; Istiqomah (Indonesian Journal of Law and Economics Review, 2025)
Background: The rapid expansion of social media has transformed marketing practices within academic libraries, requiring adaptive strategies to maintain user engagement. Specific Background: Despite growing digital promotion, empirical evidence on how social media strategies shape library service utilization remains limited. Knowledge Gap: Prior studies often emphasize platforms rather than strategic content and user response patterns. Aim: This study examines social media strategies employed by academic libraries and their relationship with user engagement and service utilization. Method: Using a qualitative approach, data were collected through observations, documentation, and interviews with librarians and users, then analyzed thematically. Results: The findings indicate that interactive content, consistent branding, and audience-oriented messaging strengthen user engagement and awareness of library services. Novelty: This research highlights strategic patterns of social media use rather than platform comparison, offering an integrated perspective on digital library marketing. Implications: The results contribute theoretically to library marketing literature and practically guide librarians in designing effective, user-centered social media strategies. Highlight & Keyword Highlights: Social media strategies shape user engagement in academic libraries Interactive content strengthens awareness of library services Strategic messaging supports sustainable digital library promotion Keywords: Social Media Marketing, Academic Libraries, User Engagement, , Library Services, Digital Promotion